Challenges and Opportunities for Non-Cash Payments in the Era - Annysha Basir; Muchriana Muchran (International Journal of Economic Research and Financial Accounting, 2025)
This research aims to find out more deeply about the challenges and opportunities of non- cash transactions. The research method used is library research, namely research activities carried out using library data collection methods, reading and taking notes and processing research materials. Literary study also means data collection techniques by reviewing books, literature, notes, and various things related to the problem you want to solve. Data collection techniques include reviewing research journals or scientific articles, books, documents and information related to research. Technological developments have encouraged businesses to carry out financial businesses using digital technology or in other words financial technology and the importance of understanding the complexity of non-cash payments in the context of the modern economy because digital transformation is not only a transition from traditional banking to the digital world, but also a major shift in the way banks operate. and other financial institutions learn, interact and satisfy customers. The challenges faced during non-cash transactions are the nature of community dependency, data security, inadequate community infrastructure and so on. Meanwhile, the opportunity to use non-cash transactions is that it makes office work easier, accountable, structured and supports financial inclusion.